CITRA KAUM PEREMPUAN DI HINDIA BELANDA - Hidayani, Fika; Hardini, Isriani (IAIN Pekalongan, 2016)
This article illustrates the position of Indonesian women in the Dutch colonial era, where women were treated arbitrarily, and they did not have the rights as human beings which equal to men. In fact, due to economic conditions and necessity, these women were willing to become a mistress and housekeeper in the Dutch household in Indonesia. This article is an interesting to discuss because the condition of women in Dutch colonial are rarely exposed to the media. A condition that was very dramatic that never happened again to women in Indonesia.Artikel ini menggambarkan mengenai kedudukan perempuan Indonesia ketika zaman penjajahan Belanda, di mana perempuan diperlakukan semena-mena, dan tidak diberikan haknya sebagai manusia yang sederajat dengan kaum pria. Bahkan dikarenakan kondisi ekonomi dan keterpaksaan, para perempuan ini rela menjadi gundik dan nyai bagi rumah tangga orang Belanda yang tinggal di Indonesia. Artikel ini menarik dibahas karena kondisi perempuan seperti ini jarang terekspos media. Suatu kondisi yang sangat miris yang diharapkan tidak akan terjadi lagi pada perempuan di Indonesia.